The Role of Entrepreneurial Strategies of the Moi Tribe in Developing Local Businesses in Sorong Regency - Folce Elden Palyama (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to examine the role of entrepreneurial strategies implemented by Moi entrepreneurs in developing local businesses in Sorong Regency. Using a qualitative approach with a case study method, this research gathered data through in-depth interviews with Moi entrepreneurs and community leaders, supported by observations. The results indicate that the Moi entrepreneurial strategy is multifaceted, combining local wisdom (utilization of kinship networks, natural resource management) with adaptation to modern elements (improved product quality, use of simple technology). This strategy plays a crucial role in maintaining business sustainability, increasing competitiveness, and empowering the local economy. However, further business development is hampered by challenges such as limited access to capital, managerial knowledge, infrastructure, and suboptimal policy support. This study concludes that targeted interventions that strengthen existing strategies and address existing obstacles are crucial to maximizing the contribution of Moi entrepreneurship to the regional economy.